Effects of changes in banking and exchange control legislation in the United Kingdom on the significance of the money aggregates as indicators 1971-81 - ARGY, V. (PSL Quarterly Review, 2013)
In an effort to exercise greater control over inflationary pressures in the United Kingdom the authorities have increasingly attempted to control the growth in monetary aggregates. However, the decade in which these controls have been in force has witnessed an unprecedented degree of change in the authorities' control over the banking system. The impact of these changes has undoubtedly made attempts to control monetary aggregates more difficult and complicated. These changes are divided into eight distinct phases in an attempt to show how they may have distorted monetary aggregate indicators. JEL: E52, E31